2016
DOI: 10.1016/j.ijid.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Management of infections in critically ill returning travellers in the intensive care unit—I: considerations on infection control and transmission of resistance

Abstract: Depending on their destinations and activities, international travellers are at a significant risk of contracting both communicable and non-communicable diseases. On return to their home countries, such travellers may require intensive care. The emergence of severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV), and more recently Ebola haemorrhagic fever, has highlighted the risks. Other well-known communicable pathogens such as methicillin-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…Fever with cough and SOB, then fever with cough were the most common symptoms among patients (20.5% and 15.3%, respectively). These findings are consistent with previous reports [21,22,38,[42][43][44][45][46][47]. Notably, the clinical features of MERS-CoV infection ranged from asymptomatic or mild disease to acute respiratory distress syndrome and multi-organ failure, which is consistent with the findings of previous studies from various countries [33,34,40,43,47,48].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Fever with cough and SOB, then fever with cough were the most common symptoms among patients (20.5% and 15.3%, respectively). These findings are consistent with previous reports [21,22,38,[42][43][44][45][46][47]. Notably, the clinical features of MERS-CoV infection ranged from asymptomatic or mild disease to acute respiratory distress syndrome and multi-organ failure, which is consistent with the findings of previous studies from various countries [33,34,40,43,47,48].…”
Section: Discussionsupporting
confidence: 93%
“…Dromedary camels have been implicated due to reports that some confirmed cases were exposed to camels. In the Middle East, confirmed cases of MERS-CoV have arisen as sporadic, familial, or hospital clusters [13,[22][23][24][25][26]. Although human-to-human transmission of MERS-CoV has been identified in many European, African, and Middle Eastern countries, [27][28][29][30] a genomic analysis of the Riyadh MERS-CoV isolates suggested that there were three genetically distinct lineages of MERS-CoV; therefore, it was unlikely that the Riyadh infections were the result of a single, continuous chain of human-to-human transmission [15,31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En caso de no evidenciarse hemorragia espontánea hay que iniciar el tratamiento de soporte vital y farmacológico empírico sin esperar a los primeros resultados microbiológicos 11 . Además de la corrección hemodinámica con cristaloides/coloides, hay que tener en cuenta lo siguiente:…”
Section: Neurológicosunclassified
“…In adults, respiratory viruses account for 10% to 40% of CAP and the most common of these are influenza, parainfluenza, adenovirus and respiratory syncytial viruses (RSV) [1,2]. Influenza viruses which are classified by their core proteins (i.e.…”
Section: Viral Infectionsmentioning
confidence: 99%